AB0139 T FOLLICULAR HELPER CELLS MAY BE INVOLVED IN THE LUPUS DEVELOPMENT IN HIGH FAT DIET-INDUCED OBESITY MICE. (13th June 2020) - Quinet, R.; Zhang, X.; Meng, J.; Shi, X.; Ali, H.; Kumar, N.; Hellmers, L.; Washington, T.; Davis, W.; Zakem, J.; You, Z.
Abstract : Background: System lupus erythematosus (SLE) is an autoimmune disease that is associated with skin rash and multiple organs lesion. It is known that obesity is a major factor contributing to the onset and progression of autoimmune diseases including SLE. Our previous study showed that circulating T follicular helper (Tfh) cells played an important role in autoantibody production in SLE patients. A recent study showed that Tfh cells promote B cell production of IgA antibodies, which help shape the composition of the gut microbiota and may modulate obesity. Objectives: By establishing an obesity-associated lupus mouse model, we investigated the pathophysiologic link of obesity, SLE and Tfh cells using MRL/lpr lupus prone mice. Methods: Twenty MRL/lpr mice (10 male and 10 female) were randomized equally fed with a regular diet (RD) or high fat diet (HFD, 60% calories comprised of fat). Their body weights were recorded weekly as an indicator of obesity achievement. SLE progression was monitored weekly by development of skin lesion and urine protein levels assessed by Bradford assay. Blood was collected for IgG, anti-dsDNA and anti-nuclear antibody (ANA) detection. At the endpoint of week 14, spleen was measured and weighted. Spleen, kidney, and dorsum of neck skin were collected and embedded for H&E, PAS, Masson's staining, and immune complex staining to detect active histopathological lupus lesions and be quantified as histological skin score and kidney index. Tfh cells in spleen was identified by immunohistochemistry (IHC) staining glomerulus of kidney. Results: Obesity was achieved with a significant difference of mouse body weight between the RD and HFD groups by week 3 and continued until week 14 ( p <0.05 to p <0.01). Evidence of SLE development, such as skin rash on the dorsal neck and back in HFD group showed up as earlier as week 6 and occurred in 55.6% of the HFD group vs 11.1% of the RD group ( p <0.05), with a higher histological score of skin in HFD group ( p <0.05). Proteinuria was increased from 11 to 14 week in male HFD group with an elevated kidney index and immune-complex deposits in their glomerulus of kidney. There was an increase trend of anti-dsDNA and IgG titer in HFD group, but no difference of ANA was observed between these two groups. Splenomegaly was observed in the HFD mice ( p <0.05). The Tfh cells in the spleen of HFD group were higher than RD group. Conclusion: Our results show accelerated and greater severity of lupus development in MRL/lpr mice with HFD compared to mice on RD, indicating HFD-induced obesity exacerbates lupus development in mice. Tfh cells may be involved in the relation of SLE and obesity. This model could be used to investigate the mechanism underlying the link between obesity and SLE development. Interventions to reduce body weight or target Tfh cells may improve both lupus symptoms and outcomes in genetically predisposed SLE patients. References: [1]Tedeschi S, et al. Obesity and the risk of systemic lupus erythematosus among woman in the Nurses' Health Studies. Semi in Arth and Rheu. 2017, 47:376-383 [2]Cozier YC, et al. A prospective study of obesity and risk of systemic lupus erythematosus (SLE) among Black woman. Semi in Arth and Rheu. 2019, 48:1030-1034 [3]Wang G, et al. Differential oxidative modification of proteins in MRL+/+and MRL/lpr mice: Increased formation of lipid peroxidation-derived aldehyde-protein adducts may contribute to accelerated onset of autoimmune response. Free Radic Res. 2012, 46(12):1472-1481 [4]Seth A, et al. Spatial and functional heterogeneity of follicular helper T cells in autoimmunity. Current Opinion in Immunology. 2019, 61:1-9 5.Petersen C, et al. T cell–mediated regulation of the microbiota protects against obesity. Science. 2019, 365 (6451): eaat9351 Disclosure of Interests: None declared